Defining legal technology and its implications. (5th April 2022) - Whalen, Ryan
Abstract: Legal technological developments have been both lauded as the promising future of the law and derided as a danger to the fundamentals of justice. This article helps reconcile these divergent perspectives by providing a definition of legal technology and a framework through which to understand its different types and their potential implications for the legal system and society more generally. Mapping technologies according to how specifically they afford legal uses, and the directness with which they engage in unmediated legal activities reveals different technological categories and their differing propensities to have legal, functional or general implications. This framework can help inform discussions both about which types of legal technologies to be excited about, and which to be concerned about, while also helping guide research, policymaking, design and adoption considerations.